The Influence of Healthy Lifestyle, Brand Trust and Product Quality on Purchasing Decisions on Herbalife Nutrition Products - Shahirah , Nabilah Veti; Akhiruddin, Anita (Fakultas Ekonomi, Universitas Muslim Indonesia, 2025)
The purpose of this study is to analyze the influence of healthy lifestyle variables, brand trust and product quality partially and simultaneously on purchasing decisions for Herbalife Nutrition products. The population in this study were all consumers who had used Herbalife products at least once in the Gresik area. The analysis method in this study used primary data with a total of 150 respondents and accidental sampling techniques. The tests used were validity, reliability test, normality, multicollinearity, heteroscedasticity, multiple linear regression, f test, t test, and coefficient of determination test. This study concludes that healthy lifestyle, brand trust and product quality partially have a positive and significant effect on purchasing decisions.